THE ANONYMOUS EDUCATOR - MERCEAN-ŢÂRC, Mirela (Studia Universitatis Babes-Bolyai Musica, 2018)
This paper aims to highlight the important role of the family and community in the process of educating children in the archaic Romanian village. The Anonymous Educator was represented by these two forums (family and community) which used to establish the typology of the behaviour, the moral, spiritual and artistic standards in the community, which the children, during the millennia, would learn empirically by participating in the daily events. This kind of natural, empirical education disappeared today, due to the disintegration of the structures of the traditional village. The lesson of the Anonymous Educator is a moral, spiritual one, a lesson which shapes strong consciences and perennial values. It can be a model for learning music by the songs specific to the spirituality of the children from diverse cultural areas, as well as a moral model for the contemporary society.